Pengaruh Religiusitas terhadap Kebahagiaan pada Mahasiswa Institut Agama Islam Tribakti Kota Kediri - Hikmatun Nafi’ah; Abd. Basith Arham (Journal of Theory and Practice in Islamic Guidance and Counseling, 2024)
Happiness is something that everyone longs for, and various ways have been undertaken just to experience it. Happiness is closely related to one's religiosity; when one is able to express gratitude, they can more easily achieve happiness. However, many factors contribute to a person's happiness beyond religion. Based on this, the research question in this study is whether there is an influence of religiosity on the happiness of Institut Agama Islam Tribakti Kota Kediri students. The method used in this research is quantitative analysis with Multiple Regression. The independent variable is religiosity, while the dependent variable is happiness. The population in this study consists of 1,597 Institut Agama Islam Tribakti Kota Kediri students, with a sample size of 278 students. The instrument used in this study is a scale based on aspects of religiosity and happiness. Data collection was conducted using a questionnaire. Data analysis was performed using simple linear regression and SPSS. 21. The results of the study indicate that religiosity affects happiness, and there is a significant influence. These findings have practical implications for Institut Agama Islam Tribakti Kota Kediri. The university could consider strengthening religious programs and providing greater spiritual support for students. By enhancing aspects of religiosity, the university can help students achieve better emotional and psychological well-being.